Implementasi Multi Server Data Storage Pada Cloud Computing - Jasnica Huang; Yuli Fitrisia; Muhammad Arif Fadhly Ridha (Jurnal Komputer Terapan, 2018)
The need of information that is always up-to-date and accessible anywhere and anytime is increasing now. It causes the need of cloud services in the form of high availability data storage. With high availability, it can reduce the occurrence of server failure. One way to improve the quality of the service is to implement multi server data storage. The implementation needs some techniques such as data replication, load balancing and failover. Data replication uses GlusterFS, load balancing uses HAProxy and failover uses Heartbeat. The result of this research found that the average data successfully uploaded 84.5 % and downloaded 100% from data storage. The failover method obtained 66.67% an average success rate in making the switch even one of the server failed, then the spread of the request is split evenly 50:50 by load balancing. Meanwhile, server performance shows that service delays are categorized in "Very Good" and throughput is categorized in "Good".